2020
DOI: 10.1186/s12872-020-01737-1
|View full text |Cite
|
Sign up to set email alerts
|

Validation of myocardial infarction diagnosis in patients with congenital heart disease in Sweden

Abstract: Background The population of adults with congenital heart disease (CHD) is growing, and increasingly more patients with CHD reach older ages. Patients with CHD are at an increased risk of myocardial infarction (MI) with increased age. Diagnosing MI in patients with CHD can be challenging in clinical practice owing to a high prevalence of aberrant electrocardiograms, ventricular hypertrophy, and heart failure, among other factors. The National Swedish Patient Register (NPR) is widely used in epi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 48 publications
(50 reference statements)
0
5
0
Order By: Relevance
“… 22 In a recent study by Fedchenko et al, CHD diagnosis in the National Swedish Patient Register was validated for patients with both CHD and myocardial infarction diagnoses and showed a positive predictive value for CHD of 74·8%, similar to findings in other studies that have validated other diagnoses in the National Swedish Patient Register. 30 …”
Section: Discussionmentioning
confidence: 99%
“… 22 In a recent study by Fedchenko et al, CHD diagnosis in the National Swedish Patient Register was validated for patients with both CHD and myocardial infarction diagnoses and showed a positive predictive value for CHD of 74·8%, similar to findings in other studies that have validated other diagnoses in the National Swedish Patient Register. 30 …”
Section: Discussionmentioning
confidence: 99%
“…However, a previous study of patients with CHD with myocardial infarction showed only slightly lower validity of the CHD diagnosis compared with that in the previous study. 20 …”
Section: Discussionmentioning
confidence: 99%
“…However, data from Swedish registries have been shown to be highly accurate (14). Although data on validation of cardiac defects are limited, a study from Denmark, with a similar health care system as Sweden, reported a positive predictive value of 90% for cardiac birth defects (34) and a Swedish study assessing congenital cardiac defects in patients with myocardial infarction found a 74.8% accuracy specifically regarding diagnosis of congenital cardiac defects (35). Although we did not have data on folic acid supplementation or serum levels during pregnancy, as well as severity of CeD or adherence to a gluten-free diet, these variables would have been of greater importance had we detected a positive association between maternal CeD and congenital birth defects (which we did not).…”
Section: Discussionmentioning
confidence: 99%